El Excentrico, 1965-07-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
July 20, 1965 [20 de Julio de 1965]. Ano 15, No 19. Cover has a photographs of three fashion models, Gloria de la Rosa, Linda Mena, and Suzanne Gutlerrez in white gowns, holding trophies. Rosa, who has won the title of Amercian GI Forum State Queen, is holding a flower bouquet.